Neuroprotection and Oxidative Stress Reduction by Bacillus coagulans: An in vitro Comparison with Escitalopram - Siddappa, Usha Dhoddametikurke; Suresh, Mandara Mathighatta; Katchhi, Mohd Sharique; Baraka, Babiker Bashir Haroun; Muralidhar, Shilpashree Bettadapura; Basavaraju, Chinthana Handankere; Aditya, Chakure; Murthy, Jyothi; Jayaramu, Rajamma Abburu (International Journal of Pharmaceutical Investigation, 2026)
Background Neurodegenerative and psychiatric disorders are often linked to oxidative stress and mitochondrial dysfunction, necessitating novel therapeutic strategies. Bacillus coagulans, a probiotic known for its role in gut-brain axis modulation, has been investigated for its potential neuroprotective and antioxidant properties. Assessing its effects on neuronal cell viability and oxidative stress may provide valuable insights into its therapeutic potential. This study aims to evaluate the cytotoxicity and oxidative stress modulation of Bacillus coagulans in SH-SY5Y neuroblastoma cells. Materials and Methods Escitalopram was used as a standard to compare its potential neuroprotective and antioxidant effects. Cytotoxicity studies on SH-SY5Y were assessed by MTT Assay at 5 different concentrations. Oxidative stress levels were analyzed using ROS (DCFDA) to evaluate antioxidant activity. Escitalopram was used as a reference standard for comparative analysis. Results Bacillus coagulans exhibited minimal cytotoxicity at all tested concentrations, with SH-SY5Y cell viability remaining high and comparable to untreated controls. The MTT assay confirmed a concentration-dependent response, but no significant toxicity was observed at physiologically relevant doses. In ROS assays, Bacillus coagulans treatment led to moderate suppression of ROS generation in SH-SY5Y cells exposed to oxidative stress, with antioxidant effects closely matching those of escitalopram. Fluorescence imaging and quantification revealed that Bacillus coagulans effectively attenuated oxidative stress without compromising cell viability. Conclusion The study provides insights into the effects of Bacillus coagulans on neuronal cell survival and oxidative stress modulation. Observed cytotoxicity and antioxidant activity suggest its potential neuroprotective role, supporting its relevance in neurological health. The findings highlight the neuroprotective and antioxidant potential of Bacillus coagulans in SH-SY5Y cells. Its ability to regulate oxidative stress may contribute to novel therapeutic approaches for neurodegenerative and psychiatric disorders, warranting further investigation.
Keywords: Bacillus coagulans; Oxidative stress; SH-SY5Y; Escitalopram.